Ben-Gurion's political struggles, 1963-1967 : a lion in winter - Shalom, Zaki (Cass series--Israeli history, politics, and society ;, 2006)
"With insight into one of the principal figures of Zionism and modern Israel, this book explores David Ben-Gurion's political career in the years leading up to the Six-Day War and details many of the crucial issues and events the world is still grappling with. This book traces David Ben-Gurion's waning years in the Israeli political arena. After his resignation from the office of prime minister in 1963, the "Old Man" soon lost faith in his self-chosen successor, Levi Eshkol, and ceaselessly tried to undermine the latter's premiership, eventually forming a breakaway party."--Jacket.